Free energy landscape of a minimalist salt bridge model. (2nd September 2015) - Li, Xubin; Lv, Chao; Corbett, Karen M.; Zheng, Lianqing; Wu, Dongsheng; Yang, Wei
Abstract: Salt bridges are essential to protein stability and dynamics. Despite the importance, there has been scarce of detailed discussion on how salt bridge partners interact with each other in distinct solvent exposed environments. In this study, employing a recent generalized orthogonal space tempering (gOST) method, we enabled efficient molecular dynamics simulation of repetitive breaking and reforming of salt bridge structures within a minimalist salt‐bridge model, the Asp‐Arg dipeptide and thereby were able to map its detailed free energy landscape in aqueous solution. Free energy surface analysis shows that although individually‐solvated states are more favorable, salt‐bridge states still occupy a noticeable portion of the overall population. Notably, the competing forces, e.g. intercharge attractions that drive the formation of salt bridges and solvation forces that pull the charged groups away from each other, are energetically comparable. As the result, the salt bridge stability is highly tunable by local environments; for instance when local water molecules are perturbed to interact more strongly with each other, the population of the salt‐bridge states is likely to increase. Our results reveal the critical role of local solvent structures in modulating salt‐bridge partner interactions and imply the importance of water fluctuations on conformational dynamics that involves solvent accessible salt bridge formations.